Antibióticos associados ou não ao cloprostenol sódico para tratamento de infecções uterinas puerperais em vacas leiteiras - SOARES, Moises M. (2015)
It aimed to evaluate, the effectiveness of two antibiotics, associated or not to the sodium cloprostenol in treatment of retention of cows’ placenta. The animals have been randomly divided into the following treatments: Treat. 1: cefquinoma (n=25) 1ml/25kg PV (25 mg/ml) – Intramuscular – once a day, during three days; Treat. 2: cefquinoma (n=25) 1ml/25kg PV (25 mg/ml) – Intramuscular – once a day, during three days, plus 2ml of sodium cloprostenol (0,250 mg/ml) in the 1st and 3rd day of treatment (n=25) animals; Treat. 3: oxytetracycline (n=25), 20mg/kg PV of oxytetracycline hydrochloride – Intramuscular – during two days with a gap of 48h; and Treat. 4: oxytetracycline associated to the sodium cloprostenol (n=25), 20 mg/kg PV of oxytetracycline hydrochloride – Intramuscular – during two days with a gap of 48h, plus 2ml of sodium cloprostenol (0,250 mg/ml). In the 1st and 3rd day of treatment. After the treatments, the animals have been evaluated relating to the increase of temperature (over 39,0 ºC) and the need of supportive care through the 1st week after the birth. The animals were re-evaluated between the 3rd and 5th postpartum weeks, by the rectal palpation, ultrasonography and vaginoscopy, to measure the presence and level of the uterine infection. It has evaluated the rate of conception at the 1st insemination, the number of pregnant animals on the 60, 90, 120 and 180 postpartum days, the average number of labors/conceptions and labor periods. The experiments were organized in DIC. The variables were submitted to a normality test and the averages were compared by Chi-square or Tuckey’s tests. The treatments with cefquinoma associated or not to the sodium cloprostenol presented better results (P<0,05) relating to the increase of temperature. The need of additional treatments and presence of uterine infection were bigger in the animals that received only oxytetracycline (P<0,05). For the same antibiotic, the association with cloprostenol has not interfered into these variables (P>0,05). There was not effect of treatments in the % of pregnant animals in the 1st IA and into the numbers of births by conception (P>0,05). The animals treated only with oxytetracycline presented worst period of births (P<0,05). It concludes that the treatment with cefquinoma is more efficient. The oxytetracycline applied alone, not associated to the cloprostenol gives the worst results.